(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the theoretical and methodological foundations of preparing students for professional and pedagogical activities based on an axiological approach. Also today, the issues of using a value-based approach in the training of future personnel and the development of their professional knowledge and skills were analyzed.